Short-term spinal cord stimulation is an effective therapeutic approach for herpetic-related neuralgia—A Chinese nationwide expert consensus - Sun, Wuping; Jin, Yi; Liu, Hongjun; Yang, Dong; Sun, Tao; Wang, Yaping; Fan, Yinghui; Fan, Xiaochong; Jin, Xiaohong; Wan, Li; Gu, Ke; Feng, Zhiying; et al. (Frontiers in Aging Neuroscience, 2022)
Short-term spinal cord stimulation (st-SCS) has been widely used to treat herpetic-related neuralgia (HN) in China for several years, but is still heavily debated as it has no strong evidence in clinical application. Therefore, a questionnaire survey among the Chinese pain specialist workgroup of the Chinese Neuromodulation Society and Chinese Medical Doctor Association was carried out to achieve a consensus about the clinical use of st-SCS for HN. The contents of the questionnaire include basic information about doctors (training, hospital level, work experience, procedure numbers, etc.), efficacy, indications, and contraindications of st-SCS, operation conditions, and preoperative preparation of st-SCS, and the prospect of the st-SCS procedure. Initially, the survey was conducted on 110 experts who have practiced the st-SCS procedure from all over the provinces in China. Finally, valuable data was calculated from the 110 questionnaires excluding the doctors with less than one year of experience of st-SCS, less than ten cases of procedures per year, and no standard training in SCS technique. Based on the 110 questionnaires, it is estimated that 5,000 to 10,000 cases of electrical stimulation are carried out nationwide each year. 69 valid questionnaires acquired from senior pain physicians were more valuable and specialized in the efficacy, indications, and contraindications of st-SCS for HN. It was commonly agreed (97.10%) that the HN patients with less than 3 months will obtain good effectiveness (patient satisfaction rate≥50%). Almost all (98.55%) agreed that the st-SCS can be used in SHN patients, there was a common agreement (72.46%) that AHN patients are an indication of st-SCS and more than half agreement (53.62%) that st-SCS may be fit for early PHN (3-6 months). A common agreement (79.71%) was achieved that more than half of HN patients had the experience of nerve block or nerve pulsed RF. A similarly large number of experts 57/69 (82.61%) agreed that an 80% paresthesia coverage should be achieved at the test stimulation and 57/69 (82.61%) agreed that the treatment of st-SCS need be persistent for 1-2 weeks. Early HN patients can get an effective outcome from the treatment of st-SCS and maybe the indication of st-SCS.